INOVASI KEBIJAKAN DAN PROGRAM PENINGKATAN MUTU PENDIDIKAN ISLAM - Zuriati; Nasroh; M. Sobry (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Islamic education plays a strategic role in shaping students’ character and moral values amidst the dynamics of global development. However, challenges such as modernization, human resource quality, and curriculum relevance demand continuous policy and program innovation. This article explores various policy innovations and quality improvement programs in Islamic education implemented by governments, educational institutions, and communities. The approach includes policy analysis, literature review, and empirical examination of field implementation. The findings indicate that the success of Islamic education quality improvement depends on the synergy between adaptive policies, teacher competency enhancement, digital technology utilization, and active community participation. The study recommends the importance of locally based policy reform, digital learning innovation, and continuous evaluation to ensure Islamic education remains relevant, inclusive, and competitive.